Grease [videorecording (Blu-Ray)] - Kleiser, Randal; Travolta, John, 1954-; Newton-John, Olivia; Channing, Stockard; Jacobs, Jim; Casey, Warren (Paramount, 2017)
Film version of the musical about high school life in the 1950s.